The Influence of Beliefs, Attitudes, Subjective Norms, and Behavioral Control Perceptions of the Entrepreneurial Intentions of Students of SMK Negeri 1 Slawi - Hardianto, Rio Noverdhi; Kardoyo, Kardoyo; Wahyudin, Agus (Journal of Economic Education, 2020)
The purpose of this study was to determine a) the influence of beliefs, attitudes, subjective norms and perceptions of behavioral control on entrepreneurial intentions; b) the influence of trust on attitudes, subjective norms and perceptions of behavioral control; c) the influence of trust on entrepreneurial intentions through entrepreneurship attitudes, the influence of trust on entrepreneurial intentions through subjective norms, and the influence of trust on entrepreneurial intentions through the perception of behavioral control of students of SMK Negeri 1 Slawi. The results of this study are a) trust has no effect on student entrepreneurial intentions, entrepreneurial attitudes, subjective norms, behavioral control perceptions, have a positive and significant effect on entrepreneurial intentions. b) trust has a positive and significant effect on entrepreneurship attitudes, subjective norms, and perception of control c) trust influences entrepreneurial intentions through entrepreneurship attitudes, trust influences entrepreneurial intentions through subjective norms and trust influences entrepreneurial intentions through behavioral control perceptions.